(untitled) (Studia Iberystyczne, 2014)
The article discusses the construction of identity in the novel A Journey with Rupert by Brazilian writer Salim Miguel in relation to the problems of migration and multiculturalism. The analysis focuses on the aspects which determine the double identity of the immigrant characters: the culture of the native country in comparison to that of the foreign country; religious beliefs; family relations models; the diaspora experience (both empirical and mental) by different generations of immigrants; the preservation or alteration of the mother tongue at the contact with the new linguistic reality; the dialogue between the immigrants’ little narratives and the grand narrative of Brazil.